26 Opportunistic infections in inflammatory bowel disease: are we adhering to the ecco guidelines?. (5th April 2017) - Reed, O; Bradley, N; Hall, R; Bhat, S
Abstract : Background: The use of immunomodulators for inflammatory bowel disease (IBD) has significantly improved disease management. However, these treatments increase the risk of infection. Screening for immunity to serious infection is recommended but compliance with these recommendations is unknown. Aim: To assess adherence to the European Crohns and Colitis Organisation (ECCO) screening guidelines and the rates of developing opportunistic infections in a cohort of IBD patients. Method: All patients currently on biological therapy were identified from a database of IBD patients within the Southern Health Trust. Case records were retrospectively reviewed to identify compliance with screening guidelines, and subsequent development of opportunistic infection. Results: 78 patients were receiving biologics +/− immunomodulators. 62 (79.5%) of patients had Crohn's disease. The majority were pre-screened appropriately for infection (77.9%) with 99% of patients being pre-screened for TB. 72.8% of patients had the recommended viral serology checked. Six patients (7.69%) developed infections. The majority did not require hospital admission (66. 7%). Two patients (33.3%) developed sepsis requiring hospital admission. There was no mortality related to infection. Infection was more frequent in patients that were on both an immunomodulator and biological therapy (11.9% vs 2.8%, p=0.13) than biological therapy alone. No patient developed, was treated for or reactivated latent tuberculosis. Conclusions: In this IBD cohort screening for infection was appropriate but could be further optimised. Risk of infection in this cohort was lower than in previous studies. Better adherence to screening recommendations and vigilance for infection may reduce the morbidity associated with immunosuppression in IBD.